Penerapan Sanksi Pidana Terhadap Peredaran Sediaan Farmasi Obat Tanpa Izin Edar Berdasarkan Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan (Studi Kasus Putusan Nomor: 02/Pid.Sus/2016/PN.Skt dan Putusan Nomor: 136/Pid.Sus/2015/PN.Skt) - SARI, INDAH KURNIA, HARTANTO, S.H., M.Hum (2017)
The circulation of drugs without marketing authorization in Indonesia is increasingly prevalent. One of the government's commitments in tackling the widespread circulation of drugs without a marketing authorization is with the enactment of Law No. 36 of 2009 on Health. In the application of criminal sanctions rules on distribution of pharmaceutical drugs without a marketing authorization under Article 106 and 107 of Law No. 36 of 2009 on Health. In this research there are three problems: How the application of criminal sanctions, the second how the consideration of the judge in the verdict, and the third how preventive efforts. Researchers used normative juridical method that is the way the procedures are used to solve the problem by examining the secondary data research first and then proceed to conduct research on primary data in the fields.